2012
DOI: 10.4172/2161-0487.1000106
|View full text |Cite
|
Sign up to set email alerts
|

Study of Emotional Intelligence and Marital Satisfaction in Academic Members of Rafsanjan University of Medical Sciences

Abstract: In today's highly stressful world the satisfaction of the married life has been decreasing. On the other hand, the people's communications and viewpoints can have the main role to increase the satisfaction. This study is conducted for evaluation of the relationships and links between the factors of emotional intelligence and marital satisfaction in Academic members of Rafsanjan University of Medical Sciences. 122 people of our statistical universe have answered to the social emotional intelligence of Baron and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Batool and Khalid (2009) examined the effect of emotional intelligence on martial relations and evidenced that there was great importance of EI in spousal relationship. Another research conducted on academic members of Rafsanjon University Relational communication, emotional intelligence, and marital satisfaction International Journal of Research Studies in Psychology 5 indicated a strong association in between emotional intelligence and marital satisfaction (Hasani et al, 2012).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Batool and Khalid (2009) examined the effect of emotional intelligence on martial relations and evidenced that there was great importance of EI in spousal relationship. Another research conducted on academic members of Rafsanjon University Relational communication, emotional intelligence, and marital satisfaction International Journal of Research Studies in Psychology 5 indicated a strong association in between emotional intelligence and marital satisfaction (Hasani et al, 2012).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Most of them were done on anxiety disorder and substance abuse and the like (Leahy, 2007;Hasani, Naderi, Ramazanzadeh, & Pourabbass, 2014;Hasani, Tajodini, GhaedniyaieJahromi, & Farmani-Shahreza, 2014;Moosavi Nomandan, Hasani, & Hatami, 2014). However, only one research has focused solely on the differences between major depression disorder and bipolar disorder in emotional schemas.…”
Section: Introductionmentioning
confidence: 99%